Early age of onset predicts severity of visual impairment in patients with neuromyelitis optica spectrum disorder. (October 2021) - Macaron, Gabrielle; Khoury, Jean; Bena, James; Seay, Meagan; Bermel, Robert A; Cohen, Jeffrey A; Rensel, Mary R
Background: Severe residual visual loss (SRVL) is frequent in neuromyelitis optica spectrum disorders (NMOSD). Identifying higher-risk patients at onset is important to prevent disability accumulation. Objective: To determine predictors of SRVL in a large NMOSD cohort. Methods: Patient characteristics at last visual acuity (VA) evaluation were retrospectively collected. VA was scored 0: better than 20/40, 1: 20/40–20/99, 2: 20/100–20/200, and 3: worse than 20/200. SRVL was defined as a combined score (VA worst + best eye) ⩾ 4. Descriptive statistics were used to compare groups and logistic regression to evaluate predictors of VA. Results: 106 patients (mean age at disease onset (AO): 35.8 ± 16.5 years) were included. Patients with SRVL had earlier AO (mean: 26.7 vs 38.0 years) compared to non-SRVL group ( p = 0.005). Patients with AO < 21 years were more likely to have SRVL, be blind, present with binocular optic neuritis, have recurrent optic neuritis, and receive oral therapy first-line than those with AO ⩾ 21. After adjusting for race, sex, and disease duration, the odds of SRVL were 4.68 times higher in patients < 21 at disease onset (95% CI: 1.53–14.34, p = 0.007). Conclusion: Early AO predicts SRVL in NMOSD, independent of disease duration. High-efficacy therapies should be considered for first-line treatment in this group.